P29 AICD IMPLANTATION IN A PATIENT RESURRECTED FROM CARDIAC ARREST, WITH THE R / T PHENOMENON AT THE HOLTER. (18th May 2022) - Incampo, G; De Luca, V; Rizzo, D; Bux, F; Moramarco, M; Pirozzi, M; Valecce, R; Cassano, F; Bonfantino, M
Abstract: A 72–year–old woman with hypertension for thirty years, resuscitated from cardiac arrest during prosthetic surgery of the right knee in January 2020, with external heart massage and orotracheal intubation. On examination Holter performed in February 2021, presence of couples and R / T phenomenon with Lown 1B–3–4A–5 class. The patient is subjected to coronary angiography which showed only mild atheroma without stenosis hemodynamically significant of the arterial districts explored. On the Echocardiogram, FE estimated at 60%. Based on the anamnestic data and the feedback from the fifth class of Lown at the Holter, it was decided to implant a dual chamber defibrillator for secondary prevention. The vulnerable point of refractory ventricular notoriously falls below 300 msec and in the clinical case in question there is a comparison to the holter of fifth class of lown with phenomenon R on T and coupling interval of 276 msec. The precocity of the ventricular ectopias is already in itself a risk factor for MI, reinforced in the case of clincio in question from a history of resuscitated cardiac arrest in a hospital setting. Not indicated to ours opinion of the electrophysiological inducibility study, given the positive clinical history and dynamic ECG according to Holter who examines the arrhythmic phenomenon in its spontaneous and natural way of presenting itself in circadian rhythm. The reproducibility in the laboratory with the SEI, of the electrical vulnerability was in fact in the recent years downsized, due to high specificity but low sensitivity, as there is in the clinical reality of patient neurovegetative and biohumoral fluxuonary factors, which favor the induction of malignant arrhythmias and that escape the predictive laboratory analysis. Making the patient safe with the implant of the bicameral AICD resulted from a clinical – diagnostic – instrumental analysis and after extensive discussion by the heart team in our Operating Unit.